Degradation science: Mesoscopic evolution and temporal analytics of photovoltaic energy materials. Issue 4 (August 2015) - French, Roger H.; Podgornik, Rudolf; Peshek, Timothy J.; Bruckman, Laura S.; Xu, Yifan; Wheeler, Nicholas R.; Gok, Abdulkerim; Hu, Yang; Hossain, Mohammad A.; Gordon, Devin A.; Zhao, Pei; Sun, Jiayang; et al.
Highlights: Mesoscopic evolution network models. Micro-, meso-, macroscopic physical models and statistical models. Degradation science. Real materials in realistic conditions. Abstract: Based on recent advances in nanoscience, data science and the availability of massive real-world datastreams, the mesoscopic evolution of mesoscopic energy materials can now be more fully studied. The temporal evolution is vastly complex in time and length scales and is fundamentally challenging to scientific understanding of degradation mechanisms and pathways responsible for energy materials evolution over lifetime. We propose a paradigm shift towards mesoscopic evolution modeling, based on physical and statistical models, that would integrate laboratory studies and real-world massive datastreams into a stress/mechanism/response framework with predictive capabilities. These epidemiological studies encompass the variability in properties that affect performance of material ensembles. Mesoscopic evolution modeling is shown to encompass the heterogeneity of these materials and systems, and enables the discrimination of the fast dynamics of their functional use and the slow and/or rare events of their degradation. We delineate paths forward for degradation science.